2018
DOI: 10.1111/sjop.12412
|View full text |Cite
|
Sign up to set email alerts
|

The right‐side perceptual bias in aging determined in a laboratory setting and during a virtual driving task

Abstract: H€ am€ al€ ainen, H., Rashid Izullah, F., Koivisto, M., Takio, F. & Luimula, M. (2018). The right-side perceptual bias in aging determined in a laboratory setting and during a virtual driving task. Scandinavian Journal of Psychology, 59, 32-40.Spatial perceptual rightward bias which was originally described in Dichotic Listening studies seems to be a general phenomenon. This bias is age dependent, being evident in children with developing executive functions, and emerging again at older age as a function of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This was contrary to expectations and importantly, they found no difference in the laterality of collision behaviour between young and older adults. However, Hämäläinen et al [ 46 ] recently found that older, but not younger, right-lane driving Finnish adults tended to erroneously cross the lane boundary to the left during simulated driving, whilst performing a simultaneous, high-load perception task. The older adults also had a rightward perceptual bias, indicated by more erroneous rightward responses during bilateral visual target presentation, suggesting that their leftward driving error may be related to this rightward perceptual bias.…”
Section: Introductionmentioning
confidence: 99%
“…This was contrary to expectations and importantly, they found no difference in the laterality of collision behaviour between young and older adults. However, Hämäläinen et al [ 46 ] recently found that older, but not younger, right-lane driving Finnish adults tended to erroneously cross the lane boundary to the left during simulated driving, whilst performing a simultaneous, high-load perception task. The older adults also had a rightward perceptual bias, indicated by more erroneous rightward responses during bilateral visual target presentation, suggesting that their leftward driving error may be related to this rightward perceptual bias.…”
Section: Introductionmentioning
confidence: 99%
“…The constructional apraxia uncovered by the CFT was not secondary to visual agnosia as evidenced by the DROT findings. Although the employed tasks did not constitute real life challenges, our findings may have clinical significance in patients with schizophrenia because difficulties with perceptual ( 43 ) and spatial integration along with other neurocognitive deficits may be a potential explanation for heightened rates of car accidents ( 44 ) in schizophrenics considering that proper copying cube ability ( 45 ) and left-right orientation ( 46 , 47 ) are important prerequisites for safe driving. Such deficits may relate to lateralized brain dysfunction in these patients ( 48 ) that has some basis in altered brain connectivity ( 49 ).…”
Section: Discussionmentioning
confidence: 90%
“…Further, Takio et al ., (2014) suggested that this age‐dependent rightward perceptual bias results from early development and late decline of executive functions, that is, changes in the interaction between perceptual and executive functions (Hugdahl, Westerhause, Alho, Medvedev, Laine & Hämäläinen, 2009; Takio et al ., 2014). Hämäläinen, Rashid Izullah, Koivisto, Takio and Luimula (2018) further demonstrated similar right‐side bias in the old group by utilizing an ecologically more valid (virtual reality (VR) headset based) driving simulator task.…”
mentioning
confidence: 88%